(3JGQjN GHf GdLPQjs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3GdPgHj,J (B748 (3g` s ((3COQfg s)
(3ChdgG (B:s
(3hHYO aEf GdYde HGdJGQjN Yde Ldjd s
(3BNQgG (B:s
(3bdJ (B: (3hgPG BNQ eG dNUJg ef JGQjN MGaX GdESdGe GdPgHj haQZJ efg ai jhe GdLeYg QGHY TgQ QLH SfI KeGf hJSYjf hSHYeGFI HeOjfI CfWGcjI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs